PELAKSANAAN SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMA NEGERI 6 BONE - Haslindah Indah; Sitti Habibah (UNM (Universitas Negeri Makasar), 2022)
The purpose of the study was to determine the implementation of principal supervision in improving teacher performance at SMA Negeri 6 Bone.This research approach is qualitative with descriptive research type. This research was conducted at SMA Negeri 6 Bone. Sources of data in this study were principals, vice principals and teacher. Data collecton technique in the from f interviews and documentation. the date analysis technique uses data reduction, data presentation and drawing conclusions checking the valoidity of the data using friangulation techniques. The results of the study indicate that the implementation of the principal’s academic supersion at SMA Negeri 6 Bone in improving teacher performance is to carry out a supervision program, determine schedules and make research instruments so that the process of implementing academic supervision is moreregular and clear. Furthermore, the implementation of the princlpol’s academic supervision at SMA Negeri 6 Bone in improving teacher performance is guiding teachers when experiencing difficulties in the teaching and learning process, conducting class visits to see how prepared teachers are in teaching and learning and checking the lesson implementation plan (RPP) every year. The teacher and the last is the evaluation/follow up that is carried out by the principal at SMA Negeri 6 Bone after carrying outacademic supervision is to discuss the results of teacher erross be corrected, then the principal provides guidance to teachers, both direct and indirect coaching.